Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s10877-014-9580-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of heart rate variability during auditory stimulation periods in patients with schizophrenia

Abstract: The vulnerability-stress model is a hypothesis for symptom development in schizophrenia patients who are generally characterized by cardiac autonomic dysfunction. Therefore, measures of heart rate variability (HRV) have been widely used in schizophrenics for assessing altered cardiac autonomic regulations. The goal of this study was to analyze HRV of schizophrenia patients and healthy control subjects with exposure to auditory stimuli. More specifically, this study examines whether schizophrenia patients may e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Thus, the findings of Castro et al (2008) in conjunction with other research examining diminished vagal tone among schizophrenia patients suggests that patients likely exhibit an initially "normal" sympathetic stress response, but thereafter experience difficulty recovering from the stress inducing event which subsequently leads to the maintenance of a sympathovagal imbalance characterized by an overall elevated state of sympathetic arousal and decreased parasympathetic activity. Additional HRV research assessing response to auditory stimulation produced similar results; whereby, unlike controls, individuals with schizophrenia failed to exhibit the normal expected decrease in LF HRV in the rest period following auditory stimulation (Akar et al, 2015). Interestingly, this pattern of reduced vagal tone may not be specific to schizophrenia, as depressed HRV and vagal tone have also been found among individuals with bipolar disorder (Moon et al, 2013).…”
Section: Nature Of the Sympathovagal Imbalance In Schizophreniamentioning
confidence: 81%
See 1 more Smart Citation
“…Thus, the findings of Castro et al (2008) in conjunction with other research examining diminished vagal tone among schizophrenia patients suggests that patients likely exhibit an initially "normal" sympathetic stress response, but thereafter experience difficulty recovering from the stress inducing event which subsequently leads to the maintenance of a sympathovagal imbalance characterized by an overall elevated state of sympathetic arousal and decreased parasympathetic activity. Additional HRV research assessing response to auditory stimulation produced similar results; whereby, unlike controls, individuals with schizophrenia failed to exhibit the normal expected decrease in LF HRV in the rest period following auditory stimulation (Akar et al, 2015). Interestingly, this pattern of reduced vagal tone may not be specific to schizophrenia, as depressed HRV and vagal tone have also been found among individuals with bipolar disorder (Moon et al, 2013).…”
Section: Nature Of the Sympathovagal Imbalance In Schizophreniamentioning
confidence: 81%
“…One such study in individuals with schizophreniaspectrum disorders revealed a bimodal split, whereby more than half of the patients exhibited vagal tone deficits as compared to the remaining patients, which was related to receiving a diagnosis of schizophrenia rather than schizoaffective disorder, as well as to a later age of schizophrenia onset (Malaspina et al, 1997). Later studies again examined ANS dysfunction in the context of psychosis and schizophrenia through HRV data analyses, and findings specifically demonstrated that reduced parasympathetic activity, also referred to as diminished vagal tone or decreased parasympathetic modulation, was observed among schizophrenia patients (Akar et al, 2015;Bӓr et al, 2005;Bӓr, Boettger, Berger et al, 2007;Bӓr, Boettger et al, 2008;Bӓr, Wernich et al, 2008;Berger et al, 2010;Boettger et al, 2006;Castro et al, 2008;Fujibayashi et al, 2009;Ieda et al, 2014;Iwamoto et al, 2012;Khandoker et al, 2010;Mathewson et al, 2012;Moon et al, 2013;Mujica-Parodi et al, 2005;Toichi et al, 1999;Valkonen-Korhonen et al, 2003). An overview of HRV and vagal tone findings within schizophrenia samples is presented in Table 1.…”
Section: Cardiac Autonomic Control In Schizophreniamentioning
confidence: 99%
“…Finally, the studies were subjected to meta-analysis if effect sizes could be calculated or estimated from the available data (k = 34). For 19 of the included studies both high-frequency HRV and RMSSD were available as outcomes; 16,18,21,22,24,26,[32][33][34][35][36][37][38][39][40][41][42][43][44] for 10 studies only high-frequency data were available, [45][46][47][48][49][50][51][52][53][54] and for 5 studies only RMSSD data were available. 20,25,[55][56][57]…”
Section: Resultsmentioning
confidence: 99%
“…This finding is further corroborated by the fact that we found a distinct but similar effect for two different measures of vagal activity: the RMSSD and high-frequency power. For each outcome the effect was large -for both indices in the same 35 Toichi et al (1999) 57,a Kim et al (2011) 20 Birkhoferet al (2013) 55,b Agelink et al (2001) 32 Agelink et al (2001) 21,c Jindal et al (2009) 40 Bä r et al (2008) 24,c Castro et al (2008) 16 Henry et al (2010) 39 Scholten et al (2006) 56,d Chung et al (2013) 37 Chang et al (2010) 36 Rachow et al (2011) 44 Lee et al (2011) 26 Valkonen-Korhonen et al (2003) 22 Clamor et al (2014) 38 Bä r et al (2007) 25,e Kim et al (2004) 41 Akar et al (2015) 33 magnitude -and remained stable within secondary analyses excluding studies that carried potential risk of bias. Emphasising the robustness of our findings, we analysed differences in HRV in different subgroups of patients -such as those with chronic or first-episode schizophrenia, acute in-patient or stable out-patient treatment, and use of medication.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have focused on the cardiac and auditory systems through musical stimuli [ 8 10 ]; cardiac and auditory potentials [ 11 , 12 ]; and white noise [ 13 , 14 ], indicating that there is an association between hearing bioelectrical response and HR regulation. According to the literature, more studies are necessary to confirm these findings, particularly the interaction between auditory evoked potential and cardiac autonomic regulation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%